Old Believers through the Eyes of Representatives of Other Christian Denominations in the Polish-Lithuanian Commonwealth: Jesuit Jan Aloysius Kulesha - Morozova, Nadezhda (Slavistica Vilnensis, 2020)
The initial history of the formation of the main Old Believer centers on the territory of the Grand Duchy of Lithuania (and the Polish-Lithuanian Commonwealth as a whole) has been fairly well discovered. However, the relationship of representatives of other Christian denominations of the Polish-Lithuanian state with the Old Believers is still described very fragmentarily. Usually in the scientific literature the royal secretary Piotr Michał Polttiew and a certain “bishop Antsuta” who had visited the Old Believers in the Vetka region are mentioned. At the same time, it has not yet been taken into account that representatives of the Catholic and Greek Catholic churches of the Polish-Lithuanian Commonwealth visited the Vetka’s Old Believers for missionary purposes. One of these “guests” was the Jesuit Jan Aloisy Kulesha, who tried to preach Uniate religion among the Old Believers of the Rechitsa district and described one of his visits in the treatise Wiara Prawosławna (Vilno, 1704). The purpose of this work is to introduce into scientific circulation previously unknown materials about the interest of the Jesuits of the Polish-Lithuanian Commonwealth in the person of Jan Aloysius Kulesha to the Old Believers who settled in the Rechitsa district of the Minsk Voivodeship of the Grand Duchy of Lithuania, and also to compare the information of Kulesha with the data of other “inspectors”.